(untitled) (La U Investiga, 2024)
Food care must be permanent in childhood, since as they grow, they acquire bases to have healthy habits and lifestyles. The objective was to evaluate the knowledge and healthy eating in internship homes of children from 1 to 5 years of the "Santa Anita" Child Development Center. Descriptive study, with a quantitative and cross-sectional approach; a non-probabilistic result was obtained for convenience; the instrument for data collection was CAP type (knowledge, attitudes, and practices) adapted. A pre-test was carried out before the training and a post-test. The sample was 30 people aged 21 to 41 years. Descriptive statistics were applied to the data and the main results were young adults, 60% secondary education, 63% less than a unified basic salary, and most with 2 to 3 children. The knowledge in the participants had an initial score of 8 (good) and after the training they reached 11 points (good); where applying the T-students statistic for paired samples for the comparison of means of numerical values of knowledge based on a normal distribution, P value less than 0.05 significant. Regarding the practices they used in relation to hygiene, followed by the consumption of unhealthy foods, finally they worry about the consumption of flour, sugar, and salt. It is concluded that the lack of knowledge in healthy eating in households is minimal, and with nutritional education several aspects that were unknown were strengthened.